HISTOCYTO-ARCHITECHTURAL CHANGES OF WISTER RATS SPLEEN EXPOSED TO PHOTOGRAPHIC FIXER EFFLUENT - Agbasi, Patrick Ugochukwu; Ugwu, Anthony Chukwuka; Ekezie, Jevas; Anichebe, Christian Ikechukwu (Asian Journal of Pharmaceutical and Clinical Research, 2015)
ABSRACT We investigated the effect of sub chronic low dose of radiographic fixer effluent on the cyto-architecture of Wister rat spleen. Objective: The extensive use of fixer chemicals in radiographic / radiological laboratories and the attendant discharge in to the environment of the fixer effluent especially in the developing world necessitated this study. Methods: Twentyfive (25) Wister rats that have not been used for any experiment were divided into three groups namely group 1 with 5 rats which served as control and received only water, group 2 had 10 rats and received 200mg/kg (8% LD50) of fixer effluent, while group 3 with 10 rats received 400mg/kg (16% LD50) of fixer effluent. The fixer effluents were orally administered daily for the 28 days study period. The rats were given free access to feeds and water. Two weeks study: mid way, on the 14th day of the study period (short term), 5 Wister rats each from group 2 and 3 which received (200mg/kg) and (400mg/kg) administration of fixer effluent respectively were anaesthetized, sacrificed and their spleens were harvested fixed in 10% formalin saline solution awaiting further histological preparations for short-term investigation. Four weeks study: On the 28th day of the study period (medium term), the rats in control group, and the remaining 5 rats each from groups 2 and 3 were anaesthetized and sacrificed while their spleens were collected fixed in 10% formalin saline solution for histological preparations and analysis. Results: Short term administration of (200mg/kg) fixer effluent showed inflammatory cells in the red and white pulp. The Medium term administration of (200mg/kg) fixer effluent showed infiltration of inflammatory cells in the red and white pulp and equally in the venous sinuses between the sinusoids and the parenchyma of the red pulp. Also, necrosis was recorded in the red pulp parenchyma. Short term administration of 400mg/kg fixer effluent to the rats showed slightly enlarged red and white pulp with inflammation and moderate necrosis of parenchyma of the red pulp. There was also distortion in the germinal center and trabecular. Medium term administration of 400mg/kg fixer effluent to the rats caused moderately enlarged red and white pulp with severe necrosis and lymphocytic infiltrations in the red pulp parenchyma and also infiltrations in the venous sinuses between the sinusoids and parenchyma of the red pulp. Conclusion, the fixer effluent caused deleterious effects to the cellular structure of the rat spleen. Â Key words: Fixer effluent, Wister rats, Sub chronic, Sinusoids, Inflammation, lymphocytic infiltration.